Komputerisasi Pencatatan dan Evaluasi Pelaksanaan Inseminasi Buatan di Kabupaten 50 Kota - F. E. Putra; Hendri Hendri; F. Madarisa (Universitas Andalas, 2011)
While it is not enough done in manual manner, recording is an important point to control the artificial insemination (AI) management. Then, there was an idea to carry out an arrangement of computerized AI recording and evaluation system. Its aim is to produce computer software in on-line system basis. Then it is useful in recording and evaluation of AI performance in 50 Kota district, West Sumatra as well as in decision support system. This survey and experiment combination methods used two questioners for two inseminators and four the Animal extension service officers. Secondary data were also collected from 50 Kota Animal extension services. Experiment used computers software of programming web (HTML and PHP) and database phpMyAdmin (MySQL). Variables consisted of several card, namely; (1) AI activity card, (2) pregnant inspection and infertility card, (3) Semen usage and liquid N2 stock card, (4) AI calving card which could be demonstrated by service/ conception (S/C), conception rate (CR) and calving rate indicators. The result showed that there was computer software in recording and evaluation of AI performance available for 50 Kota district. This system did recording of AI in a faster, valid, easy and qualified manner. After a local verification trial, a qualified system had been proved by using AI manual calculation comparison. Thus, this system will be more effective and efficient in AI recording and evaluation.